THE EFFECTIVENESS OF YOUTUBE TO IMPROVE STUDENTS' WRITING ABILITY OF DESCRIPTIVE TEXT AT THE GRADE X SMA N 1 ANGKOLA BARAT - Erpina, Sopi (jurnalalfa, 2024)
This research aimed to know the effectiveness of using YouTube in improving students' writing ability of Descriptive Text at the grade X of SMA Negeri 1 Angkola Barat. In this research, the researcher used one-group pretest-posttest design, there was not control group. The researcher gave pre-test to student, then, researcher gave the students’ treatment about writing Descriptive Text with video from YouTube. After treatment is given, researcher gives the student post-test. The population in this research were the students of SMA Negeri 1 Angkola Barat. The researcher used random sampling were takes class of X MIPA 2 as the sample of this research. The total of students in this class was 34 students. The score of students' before using YouTube media was 63.52 and it was categorized "fair". While the mean score of student's after using YouTube media was 76.26 and it was categorized "good". The result of both t-test was 12.513 and t-table was 1.692, it can be concluded that the used of YouTube in process learning teaching is effective and can improve students' writing ability of Descriptive Text.